Blood–labyrinth barrier damage mediated by granzymes from cytotoxic lymphocytes results in hearing loss in systemic lupus erythematosus - Zihe Zhao; Ao Li; Yan Zhu; Shaoqin Cen; Qing Liu; Yuan Zhang; Hanqi Fan; Zhenxing Hou; Dengbin Ma; Dingding Liu; Maoli Duan; Xiaoyun Qian; et al. (Proceedings of the National Academy of Sciences, 2025)
Hearing loss (HL) in patients with systemic lupus erythematosus (SLE) has been widely reported, though the underlying mechanisms remain unclear. In this study, we demonstrate significant HL in an imiquimod-induced mouse model of SLE, accompanied by blood–labyrinth barrier (BLB) damage in the stria vascularis (SV). We found that cytotoxic CD8 + T lymphocytes and natural killer cells mediate BLB disruption, with granzyme b (Gzmb) acting as the primary factor inducing cell death of the cochlear capillary endothelial cells. Remarkably, inhibiting Gzmb by Serpinb9 significantly alleviates the elevations of hearing thresholds in imiquimod-induced SLE model mice, suggesting a therapeutic target for autoimmune-related HL. Our findings provide insights into the pathogenesis of SLE-related HL and propose Gzmb inhibition as a potential therapeutic strategy.